Pengaruh Profitabilitas Dan Leverage Terhadap Kebijakan Dividen (Studi Empiris Pada Perusahaan Manufaktur Yang Listing Di Bei Pada Tahun 2016-2018) - Ana Indriyani; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstrak This research was aimed to analyze the effect of profitability (NPM) and Leverage (DER) variables on dividend policy (DPR) partially. The population used of this study is manufacturing commodity sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. In addition, the sample used of this study was purposive sampling technique. In another side, the population that contribute of this study consist of 54 data from 18 companies over 3 years period. The data collection used of this study is the documentation of the financial reports of the manufacturing companies in the consumer commodity sector listed on the IDX while the analysis used is multiple linear regression by testing the hypothesis using the T test.The results of the study explain that the variable Profitability by using a Net Profit Margin (NPM) proxy has a significant positive effect on dividend policy using a Dividend Payout Ratio (DPR) and Leverage proxy using a Debt to Equity Ratio (DER) proxy that does not have a significant effect on dividend policy utilizing the Dividend Payout Ratio (DPR) proxy.  Keyword : profitabilitas, Leverage, dan kebijakan dividen